Diagnostic accuracy of contrast enhanced ultrasound in patients with blunt abdominal trauma presenting to the emergency department: a systematic review and meta-analysis - Zhang, Zhongheng (Sci Rep, 2017)
We aimed to investigate the diagnostic accuracy of contrast-enhanced ultrasound (CEUS) in evaluating blunt abdominal trauma for patients presenting to the emergency department. Electronic search of Scopus and Pubmed was performed from inception to September 2016. Human studies investigating the diagnostic accuracy of CEUS in identifying abdominal solid organ injuries were included. Risk of bias was assessed using the QUADAS tool. A total of 10 studies were included in the study and 9 of them were included for meta-analysis. The log(DOR) values ranged from 3.80 (95% CI: 2.81–4.79) to 8.52 (95% CI: 4.58–12.47) in component studies. The combined log(DOR) was 6.56 (95% CI: 5.66–7.45). The Cochran’s Q was 11.265 (p = 0.793 with 16 degrees of freedom), and the Higgins’ I(2) was 0%. The CEUS had a sensitivity of 0.981 (95% CI: 0.868–0.950) and a false positive rate of 0.018 (95% CI: 0.010–0.032) for identifying parenchymal injuries, with an AUC of 0.984. CEUS performed at emergency department had good diagnostic accuracy in identifying abdominal solid organ injuries. CEUS can be recommended in monitoring solid organ injuries, especially for patients managed with non-operative strategy.